ANALISIS POTENSI LISTRIK DENGAN PEMANFAATAN PANAS LIMBAH BRINE DENGAN ORGANIC RANKINE CYCLE (ORC) DI SUMUR X LAPANGAN PANAS BUMI SORIK MARAPI - Melysa, Richa; Padilah, Yenni; Anwar, Irwan; Wardianto, Dedi; Afdal, Afdal (ITP Press, 2025)
The residual brine heat in the Geothermal Power Plant (PLTP) has the potential to be utilized to generate electricity because it still has a fairly high temperature and pressure. The method of utilizing residual brine heat is by using the Organic Rankine Cycle (ORC) which can be used to utilize heat at low temperatures. The main parameter method measured is the pressure and temperature in the working fluid circulation, hot water circulation (brine), and cooling water circulation. The ORC system uses an evaporator component as a replacement for the generator or boiler system in the Rankine cycle. The ORC system utilizes low-temperature heat sources such as Internal Combustion Engine exhaust heat, solar heat, biomass and brine from geothermal power plants. At low temperatures, organic fluids have higher cycle efficiency than water. The mass rate value in this study was 13.63 kg/s. where the turbine work is 328.07 Kw and the condenser heat transfer rate is 113.40 kj/s. The pump work is 311.8544 Kw. And the rate of heat transfer in the evaporator has an efficiency of 4.93% where the heat absorbed by the evaporator is 129.6213 kj/s.